PENGARUH PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013 – 2015 - Dedek Ramadhan; Gusnardi Gusnardi; RM. Riadi RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine and analyze the effect of working capital turnover on profitability in real estate and property companies listed on the Indonesia Stock Exchange. The study population is all real estate and property companies listed on the Indonesia Stock Exchange in 2013-2015 which have cash turnover data, receivable turnover, inventory turnover, and profitability as measured by return on investment (ROI) 3 years in a row ( 2013-2015). Data obtained from the Indonesian Capital Market Directory (ICMD) and the website of each company. The data analysis technique used in this study is multiple linear regression with the help of SPSS program. The results show that cash turnover, receivable turnover, and inventory turnover simultaneously affect return on investment. Partially, cash turnover has a positive effect on return on investment, receivable turnover has a positive effect on return on investment, and inventory turnover has a positive effect on return on investment.Keywords : Cash Turnover, Receivable Turnover, Inventory Turnover, and Return on Investment